Pathogenetic role of vitamin D and antimicrobial peptides in formation of recurrent bronchitis in children - Lezhenko, G.; Pashkova, O.; Gladun, K.; Kraynya, H.; Леженко, Геннадій Олександрович; Пашкова, Олена Єгорівна; Гладун, Катерина Валеріївна; Крайня, Ганна Вікторівна (Warszawa: Nowa perspektywa, 2015)
The analysis of the maintenance of a metabolite of vitamin D (25-dihydroxyvitamin D) in blood serum and level α-defensin 1-3 in sick children’s blood plasma with recurrent bronchitis was carried out. It is established that children with recurrent bronchitis reliable decrease in blood serum of concentration of a 25-dihydroxyvitamin D and increase of the contents of antimicrobial peptide cathelicidin LL-37. Decrease of the plasma level of metabolites of vitamin D in children with a recurrent bronchitis accompanies by increase of the contents of the α-defensins 1-3 in blood plasma and that could act as a padding factor of a relapsing course of a disease. The finding is a substantiation for inclusion of vitamin D in complex therapy of children with recurrent bronchitis.
Keywords: vitamin D; Vitamin-D-Bindungsprotein; cathelicidin; α-defensins 1-3; recurrent bronchitis; children